Electroless Nickel-Based Catalyst for Diffusion Limited Hydrogen Generation through Hydrolysis of Borohydride - Shannon P. Anderson; Egwu E. Kalu (Crystals, 2013)
Catalysts based on electroless nickel and bi-metallic nickel-molybdenum nanoparticles were synthesized for the hydrolysis of sodium borohydride for hydrogen generation. The catalysts were synthesized by polymer-stabilized Pd nanoparticle-catalyzation and activation of Al2O3 substrate and electroless Ni or Ni-Mo plating of the substrate for selected time lengths. Catalytic activity of the synthesized catalysts was tested for the hydrolyzation of alkaline-stabilized NaBH4 solution for hydrogen generation. The effects of electroless plating time lengths, temperature and NaBH4 concentration on hydrogen generation rates were analyzed and discussed. Compositional analysis and surface morphology were carried out for nano-metallized Al2O3 using Scanning Electron Micrographs (SEM) and Energy Dispersive X-Ray Microanalysis (EDAX). The as-plated polymer-stabilized electroless nickel catalyst plated for 10 min and unstirred in the hydrolysis reaction exhibited appreciable catalytic activity for hydrolysis of NaBH4. For a zero-order reaction assumption, activation energy of hydrogen generation using the catalyst was estimated at 104.6 kJ/mol. Suggestions are provided for further work needed prior to using the catalyst for portable hydrogen generation from aqueous alkaline-stabilized NaBH4 solution for fuel cells.